Frozen pepper pulp (Capsicum annum L.) stabilizer as soup: nutritional and sensorial assessment - Loyola, Nelson; Acuña, Carlos; Silva, Wilson; Arriola, Mariela (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2024)
The aim of this investigation was to elaborate soups from frozen pulp of organic pepper (Capsicum annum L. cv. Fyuco). Peppers were organically cultivated at the plots of Universidad Catolica del Maule, San Isidro Campus Los Niches Sector, Curico, Region VII, Chile. This research had three treatments: T0 corresponding to control treatment, T1: pepper pulp, plus stabilizer (Carrageenan Caraol PFP 5337), T2: pepper pulp, plus stabilizer and sweetener (stevia). Chemical assessments (Soluble solids (°Brix), ascorbic acid (mg.100 g-1), acidity (%) and reducing sugars (%)) and sensorial (Flavour, texture, colour, smell, appearance and acceptability) were carried out at days 0, 30 and 60. A microbiological analysis was performed by counting the total coliforms to guarantee the safety of the different treatments. The data obtained in the analyses were assessed with a completely random block design (DBCA), for the chemical and sensorial analyses, all of them having a confidence level of 95 %. There were no significant differences in the chemical parameters under study during the period of the pulp storage, sensorial analysis performed during the three times did not show significant differences.